BUSINESS REPUTATION: ORIGINAL ASSESSMENT OF KEY FEATURES IN THE CONDITIONS OF WORLD INTEGRATION OF RUSSIAN AND INTERNATIONAL LEGISLATION - Dmitrievna Akat’eva , Marina; Aleksandrovich Biryukov, Vladimir; Alekseevna Panova, Nataliia; Viktorovna Alyabeva, Elena; Mikhaylovna Zhdanova, Evgeniya (Revista Inclusiones, 2020)
Subject. The concept of business reputation and its features from different positions are presented in Russian Accounting Standards and International Financial Reporting Standards. In the conditions of global integration of accounting science, it is necessary to clarify the essence of business reputation and its classification, the specifics of formulations, and the features of subtypes. Goals/objectives. 1. An original understanding of business reputation as an economic category. 2. Identification of features of identification and evaluation of business reputation. 3. Disclosure of the essence of internally created business reputation, correction of its content. 4. Clarification of the business reputation classification. Methods. The study uses the methods of comparative analysis in relation to available scientific and theoretical results. Results. 1. An original definition of business reputation is proposed, taking into account the studied parameters. 2. The influence of the image of a company and its brands on business reputation and internally created business reputation is determined. 3. The classification of business reputation is modified. 4. The features of identification and evaluation of business reputation are specified. Conclusions/significance. 1. Identification of business reputation upon purchase and sale requires compliance with certain circumstances and/or their combination. 2. The set of qualitative characteristics that determine the internally created business reputation is subjective. 3. The image of a company and its brands is objectively included in the content of the internally created business reputation. 4. Only the calculation method as a way of evaluating business reputation is directly focused on business reputation. 5. The risk of loss of business reputation is the most relevant type of risk, reflecting the increased importance of this concept and object in the modern economy.